2018
DOI: 10.2134/agronj2017.12.0752
|View full text |Cite
|
Sign up to set email alerts
|

Cover Crop for Early Season Weed Suppression in Crops: Systematic Review and Meta‐Analysis

Abstract: W eeds occurring during early crop growth need to be removed because these are known to be most competitive with crops (Knezevic et al., 2002; Norsworthy and Oliviera, 2004; Tursun et al., 2016; Osipitan et al., 2016). Uncontrolled weeds at this early growth stage could cause irreversible and substantial crop yield losses (Knezevic et al., 2002, Adigun et al., 2014). If weeds are controlled at this time, crops can get a head start, achieve canopy closure, and compete effectively with later emerging weeds (Rajc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
113
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 155 publications
(125 citation statements)
references
References 83 publications
8
113
2
2
Order By: Relevance
“…A report showed that most studies that evaluated weed suppression by cover crops were conducted at sites with what appeared to be adequate annual rainfall (³750 mm) or with irrigation provided where rainfall was inadequate to optimize cover crop biomass production necessary for weed suppression (Osipitan et al, 2018). A report showed that most studies that evaluated weed suppression by cover crops were conducted at sites with what appeared to be adequate annual rainfall (³750 mm) or with irrigation provided where rainfall was inadequate to optimize cover crop biomass production necessary for weed suppression (Osipitan et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A report showed that most studies that evaluated weed suppression by cover crops were conducted at sites with what appeared to be adequate annual rainfall (³750 mm) or with irrigation provided where rainfall was inadequate to optimize cover crop biomass production necessary for weed suppression (Osipitan et al, 2018). A report showed that most studies that evaluated weed suppression by cover crops were conducted at sites with what appeared to be adequate annual rainfall (³750 mm) or with irrigation provided where rainfall was inadequate to optimize cover crop biomass production necessary for weed suppression (Osipitan et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Weed suppression using cover crops in conservation tillage systems was comparable with chemical and mechanical weed control in many situations, particularly at early stages of crop growth according to a recent meta-analysis study (Osipitan et al, 2018). The level and duration of weed suppression provided by…”
Section: Review and Interpretationmentioning
confidence: 96%
“…2 Even low seeding rates of fast emerging cover crops can suppress weeds during fall and spring, and provide early season weed control in the subsequent main crop. 17,18 Mixtures of cover crops performed better under dry and warm conditions than the before-mentioned single cover crop species. 19 Cover crop mixtures better compensate temporal and spatial variation in growing conditions, and thus tend to outperform single species in the long term by ensuring that at least some species grow every year at every site.…”
Section: Cover Crops In Temperate Areas As Part Of Iwmmentioning
confidence: 95%
“…Avena strigosa also produced a very dense root system in the upper soil surface and reduced root biomass of weeds and volunteer crops by 97% . Even low seeding rates of fast emerging cover crops can suppress weeds during fall and spring, and provide early season weed control in the subsequent main crop …”
Section: Cover Crops In Temperate Areas As Part Of Iwmmentioning
confidence: 99%
See 1 more Smart Citation